Some physical properties in nut and kernel of two almond varieties (‘Marcona’ and ‘Tuono’) grown in Northern Morocco - Rharrabti Y.; Sakar E. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Cultivated almonds (Prunus dulcis [Mill.] D.A. Webb) are the second fruit culture in importance after olive trees in Morocco. The present work was carried out to evaluate some physical properties in nut and kernel of two almond varieties (‘Marcona’ and ‘Tuono’) widely grown in northern Morocco. 30 fruits were collected in three marked almond trees randomly around the canopy between August, 15 and September, 10 of the 2014 season in three different sites namely Aknoul (Taza), Bni Hadifa (Al Hoceima) and Tahar Souk (Taounate). ANOVA analyses indicated that environmental effect accounted for low variation percentages for most of studied traits except nut length and kernel thickness where it explained half of variation. Genotypic effect was more important in describing variation in the majority of characters. Mean comparison revealed that no significant differences were encountered among sites for nut thickness, spherecity and kernel weight and volume. For the others traits, Tahar Souk showed the lowest values. Between varieties, ‘Marcona’ presented higher va lues for most of characters except for length and shelling percentage.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)